Rancang Bangun Aplikasi Suku Cadang Pada Toko Urip Motor Menggunakan VB.NET 2010 - Samsir, Samsir (Journal of Computer Science and Information System(JCoInS), 2020)
The process of recording the sale of spare parts and services , which includes the interaction of the company and customers and interaction with suppliers. The problem is in the process of recording sales, service is long enough, so sometimes make customers wait for a long time so that customers feel quite saturated and bored. Solousi to solve the problem is to automate customer interaction with the store is to design and build applications that record sales of spare parts and stock items based on computerized. This application generates information on sales reports, stock items, incoming goods and outgoing goods, which are equipped with a database, so that data on goods cannot be lost, which is where the application is made using the application vb.net and using MySql.